Structural multi-objective topology optimization and application based on the criteria importance through intercriteria correlation method. Issue 5 (4th May 2022) - Fan, Weichun; Xu, Zhongming; Wu, Bi; He, Yansong; Zhang, Zhifei
Abstract : A structural multi-objective topology optimization method integrating the solid isotropic material with penalization (SIMP) approach, compromise programming method and criteria importance through intercriteria correlation (CRITIC) method is proposed. The SIMP approach performs topology optimization. The compromise programming method builds a comprehensive objective function to handle the multi-objective optimization. The CRITIC method, which reflects the contrast intensity and conflicting character of objectives, is applied to determine the weight coefficients of objectives. The conceptual design of a vehicle shock tower is taken as a numerical example. Comparison of the original design and the optimized conceptual design indicates that the stiffness and frequency performance of the shock tower clearly improve as the total weight reduces. Meanwhile, comparison of the weight coefficients and corresponding optimization results produced by the subjective method, CRITIC method, grey comprehensive relational analysis and entropy weight method proves that the CRITIC method is feasible and superior in structural multi-objective topology optimization.